Hepatitis B Vaccine Non-Responders Show Higher Frequencies of CD24highCD38high Regulatory B Cells and Lower Levels of IL-10 Expression Compared to Responders - Körber, Nina; Pohl, Laureen; Weinberger, Birgit; Grubeck-Loebenstein, Beatrix; Wawer, Andrea; Knolle, Percy A.; Roggendorf, Hedwig; Protzer, Ulrike; Bauer, Tanja (Frontiers in Immunology, 2021)
Background: The cellular mechanisms involved in the lack of protective antibody response after hepatitis B vaccination are still rather unclear. Regulatory B cells (Breg) known as modulators of B-and T-cell responses may contribute to poor vaccine responsiveness. The current study aimed to investigate the role of regulatory B cells (Breg) in hepatitis B vaccine non-responsiveness after immunization with second- or third-generation hepatitis B vaccines. Method: We performed comparative phenotypic and frequency analysis of Breg subsets (CD24+CD27+ and CD24highCD38high Breg) in second-generation hepatitis B vaccine non-responders (2nd HBvac NR, n = 11) and responders (2nd HBvac R, n = 8) before (d0), on day 7 (d7), and 28 (d28) after booster vaccination. Cryopreserved peripheral blood mononuclear cells were stimulated ex vivo with a combination of CpG, PMA, and Ionomycin (CpG+P/I) and analyzed for numbers and IL-10 expression levels of Breg by flow cytometry-based analyses. Results: Flow cytometry-based analyses revealed elevated frequencies of CD24+CD27+ Breg at all time points and significantly higher frequencies of CD24highCD38high Breg on d0 (p = 0.004) and 28 (p = 0.012) in 2nd HBvac NR compared to 2nd HBvac R. In parallel, we observed significantly lower levels of CpG+P/I-induced IL-10 expression levels of CD24+CD27+ and CD24highCD38high Breg (d0: p < 0.0001; d7: p = 0.0004; d28: p = 0.0003 and d0: p = 0.016; d7: p = 0.016, respectively) in 2nd HBvac NR compared to 2nd HBvac R before and after booster immunization. Frequencies of CD24+CD27+ and CD24highCD38high Breg significantly decreased after third-generation hepatitis B booster vaccination (d7: p = 0.014; d28: p = 0.032 and d7: p = 0.045, respectively), whereas IL-10 expression levels of both Breg subsets remained stable. Conclusion: Here we report significantly higher frequencies of CD24highCD38high Breg in parallel with significantly lower IL-10 expression levels of CD24+CD27+ and CD24highCD38high Breg in 2nd HBvac NR compared to 2nd HBvac R. Anti-HBs seroconversion accompanied by a decrease of Breg numbers after booster immunization with a third-generation hepatitis B vaccine could indicate a positive effect of third-generation hepatitis B vaccines on Breg-mediated immunomodulation in hepatitis B vaccine non-responders.